contestada

1. The expression below is equivalent. 6 - 3a = 3a - 6 true or false?
2. The expression below is equivalent. 3x = 3 + x true or false?
3. The expression below is equivalent. 2(a + b) = 2a + 2b true or false?
4. The expression below is equivalent. -(4-1) = 1 - 4 true or false?
5. The expression below is equivalent. ab + cd = ba + dc true or false?

Thank you so much for the help btw!!

Respuesta :

1. False
2. False
3. True
4. True
5. True
1. The expression below is equivalent. 6 - 3a = 3a - 6 true or false?
-3a + 6 = 3a - 6
False 
2. The expression below is equivalent. 3x = 3 + x true or false?
3 * x = 3 + x
False
3. The expression below is equivalent. 2(a + b) = 2a + 2b true or false?
2 * a + 2 * b = 2a + 2b
2a + 2b = 2a + 2b
True
4. The expression below is equivalent. -(4-1) = 1 - 4 true or false?
-4 + 1 = 1 - 4
1 - 4 = 1 - 4
True
5. The expression below is equivalent. ab + cd = ba + dc true or false?
a * b + c * d = b * a + d * c
b * a + d * c = b * a + d * c 
True

:)